Lack of Information on Nutritional Status of Patients with COVID-19 Worldwide: Literature Review - Marques Bezerra, Ronney; Gabriel Monteiro Arnozo,; Luiz Carlos Francelino Silva Junior,; Rodrigo da Rosa Mesquita,; Fernanda Mayara Santos Santana,; Tatiana Farias de Oliveira,; Rafaela Campos Alcântara,; Etvaldo Rodrigues da Silva Filho,; Aisla Graciele Galdino dos Santos,; Igor Matheus Jambeiro Brandão,; Euclides José Oliveira da Cunha,; Danielly Ferreira da Luz,; et al. (Revista Portal: Saúde e Sociedade, 2021)
Objective: Nutritional factors (malnutrition and obesity) may be associated with an increased risk of worsening the health status of patients with COVID-19. This study aimed to systematize the literature about this topic. Design: Searches were carried out in Pub Med, Med Line and Scopus databases. Results: Among the 158 articles with clinical and epidemiological characteristics, 12 had variables on nutritional status, amounting 79.972 patients from five countries, 57.43% (n = 45.925) were men and the average age of the patients was 56.74 years old. The variant obesity was verified in 10 studies and malnutrition in two. Obese population in the studies was 17.937, which corresponds to a rate of 29.98% of total patients, and malnutrition population was 97, which corresponding to 41.45% of patients in the studies. Conclusions Although obesity is a risk factor for COVID-19, studies have hardly addressed the theme, focusing primarily on the USA. Malnutrition is relevant, especially in countries with greater vulnerability.